Problem-Based Learning Mathematics Modules: Their Impact on Students’ Mathematical Problem-Solving Performance - Mutiara Pertiwi; Yerizon; Ali Asmar; Yarman (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to develop a mathematics teaching module based on the Problem-Based Learning model to improve the mathematical problem-solving abilities of eleventh-grade students. Using the Plomp development model, the research was conducted through the initial investigation, prototyping, and assessment stages. The module was validated by experts in mathematics education, language, and educational technology, resulting in an average validity score of 3.56 (categorized as "Very Valid"). Practicality evaluation through classroom implementation over four meetings showed excellent practicality with an average implementation rate of 93%, while student response questionnaires revealed consistently positive feedback across all measured aspects. Effectiveness testing with 34 students showed that 73.52% achieved scores above the minimum completeness criteria, exceeding the established effectiveness threshold of 60%. This module specifically improved students' abilities in understanding problems (87.6%) and planning solutions (85.3%). Research results confirm that the developed module is valid, practical, and effective in improving mathematical problem-solving skills. This research provides educators with a structured and contextual approach to mathematics teaching that bridges theoretical concepts with real-world applications, addressing Indonesia's historical challenges in mathematics education.